Resident understanding of common acetabular fractures using 3D printed models - Singh, Mardeep Singh Pritam (2022)
Introduction Fracture of the acetabulum is usually present as complicated fracture. It requires good understanding of the fracture pattern in order to manage it. Understanding of the fracture morphology involves Radiographs and CT scans. Numerous of classifications are available to classify the fracture such as Judet and Letournel classification, yet residents and orthopaedic surgeons find it challenging. 3D printing has becoming more popular in the medical field to aid in education and management. This study was conducted to study the effect of 3D printed model in understanding acetabular fracture among orthopaedic residents with the use of Single Answer Questions (SAQs). Methodology This is an educational interventional study to evaluate the effect of the 3D printed model in the understanding of acetabular fractures among Orthopaedic residents from the Orthopaedic Department of Hospital Universiti Sains Malaysia in the year 2022 involving first to fourth year residents. All residents were screened prior attending a lecture on Acetabular Fracture. The residents then by simple randomization were divided into experimental group and control group. Control group had radiographs and CT scan while the Experimental group had radiographs, CT scan and 3D pelvic model of the associated fracture. Each group went through 5 station of cases with different acetabular fracture pattern with total of 25 single answer questions (SAQ) for assessment. The points for each SAQs were accumulated in percentage to determine the outcome. In this analysis, all categorical data were presented in frequency and percentage, while the numerical data were presented in median and interquartile range due to 3 non-normal distribution. We applied Mann-Whitney U Test in this analysis. The p-level of less than 0.05 was considered statistically significant. Statistical analysis was performed using version 26 of the SPSS software (SPSS Inc, Chicago, IL). Results There were total of 32 participants in this study. 16 in each group. It was found that median percentage of understanding in experimental group was statistically significantly higher than the control group (p = 0.021). However, it was found that median percentage of classification between experimental and control group was not significant ( p = 0.127). Conclusion The overall scores from SAQs from experimental group indicates a favourable outcome among orthopaedic resident in understanding of acetabular fracture using 3D pelvic model. Hence we recommend the application of 3D pelvic model in learning and understanding among orthopaedic residents training.